Fouling control strategy for submerged membrane bioreactor filtration processes using aeration airflow, backwash, and relaxation: a review - Yusuf, Z. (Taylor and Francis Inc., 2016)
As of today, the application of membrane bioreactors (MBRs) in wastewater treatment plants has become significantly important in various industries. The success of MBR is mainly because of the effective membrane technology used in this kind of reactor. However, membrane technology does not escape from several drawbacks, which includes high maintenance costs and fouling problems. In order to run a plant with both an optimum capability and cost, an in-depth understanding of the behavior of filtration systems is very important to the plant operator. In this paper, we review and have considered the fouling control techniques applied to submerged membrane filtration processes including hollow fiber membranes and flat sheet types of membrane filtration. The review covers the techniques involving operational parameters, such as aeration, backwashing, and relaxation. In addition, in this paper, the modeling techniques and available automatic control techniques, using stated parameters to control fouling in membrane filtration processes, are presented. The performance results of each technique are then discussed and reviewed.